INFLUENCE ANALYSIS OF REWARDS & MOTIVATION, COMMUNICATION, DEVELOPMENT, SUPPORT SYSTEM, EMPLOYEE SELECTION, EMPLOYEE RECRUITMENT, AND HEALTHY WORK ENVIRONMENT ON INTERNAL MARKETING (CASE STUDY AT PORT DIVISION BONTANG COAL TERMINAL PT INDOMINCO MANDIRI) - Syahidul Syahidul; Gusti Noortalitaria Achmad; Syarifah Hudayah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Internal Marketing is the important aspect at the organization to measure business performance. The job of internal marketing is to recruit, train and motivate employees who can serve customers well. Without being actively promoted, internal marketing can have a negative impact on service quality, which can lead to decreased customer satisfaction and profitability. This study is focused on the services division especially in port division Bontang Coal Terminal PT IMM. Researchers took research data through a Google Form questionnaire. There are 84 respondents were recorded as filling in the questionnaire to test all the hypotheses. There are 7 indicators used to assess internal marketing. The data analysis used PASW Statistics 18 to test the level of validity and reliability, to test the results of the hypothesis, the researcher used SEM PLS to determine the relationship between variables. The findings of this study are that the Rewards and Motivation, Communication, Development, Support System, Employee Selection, Employee Recruitment, and Healthy Work Environment have positive significant on Internal Marketing